"It's like he just goes off, BOOM!": mothers and grandmothers make sense of child‐to‐parent violence. Issue 2 (4th February 2016) - Williams, Megan; Tuffin, Keith; Niland, Patricia
Abstract: Child to parent violence (CPV) involves continual and cumulative abusive actions perpetrated by children and adolescents towards their parents or caregivers. This abuse produces short‐term distress and ongoing long‐term harmful consequences for parents and their families. Practitioners, researchers and policy‐makers are increasingly challenged to identify, conceptualize and respond to this form of family violence. A major challenge is that parents and caregivers under‐report this abuse so there is a lack of awareness and understanding of their psychological experiences in relation to CPV. This research adopts an interpretative phenomenological approach to explore the psychological experience of CPV. Interviews were conducted with six New Zealand mothers and two grandmothers who all experienced CPV. This abuse was experienced as an 'emotional bloody roller coaster' of unconditional love through to hatred; as 'judgement' – self‐blame and others' blame of their parenting skills; and the 'absent father' in their adolescents' lives was drawn on as an explanation for the abuse. Taken together, these psychological experiences identify the silencing of CPV is related to parents' conflicting emotions towards their children, their thoughts and feelings about themselves and how other people view them, and the impact of an absent father figure in their children's everyday lives.